The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1108/eb026941
|View full text |Cite
|
Sign up to set email alerts
|

The Dependence of Lotka's Law on the Selection of Time Periods in the Development of Scientific Areas and Authors

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 14 publications
(12 reference statements)
1
11
0
Order By: Relevance
“…His studies covered either special topics (see for example (Wagner-Döbler and Berg 1995;Wagner-Döbler 1995, 1996, 1997a), or a specific publication time period An extensive study of mathematics publications during the 19th century was performed by Wagner-Döbler and Berg (1996). This study was…”
Section: Introductionmentioning
confidence: 99%
“…His studies covered either special topics (see for example (Wagner-Döbler and Berg 1995;Wagner-Döbler 1995, 1996, 1997a), or a specific publication time period An extensive study of mathematics publications during the 19th century was performed by Wagner-Döbler and Berg (1996). This study was…”
Section: Introductionmentioning
confidence: 99%
“…In the cases examined by Lotka, the exponent Ͳ was approximately 2.0 (''inverse square law''). But later investigations showed that it lies between about 1.8 and 3.8, and that it is presumably dependent on the time period considered in the development of scientific areas [19]. With the x-values in ascending order, the function results in a hyperbolic curve or approximately in a straight line on double-logarithmic paper.…”
Section: The Place Of Mathematical Manpower and Publication Output Inmentioning
confidence: 97%
“…Furthermore, the inequality of the frequency with which scholars are able to contribute has roots in the Matthew Effect (Wagner-Döbler and Berg 1995) and the related theory of cumulative advantage proposed by Price (1976). That is, more eminent scholars are given more credit and are repeatedly rewarded by other scientists.…”
Section: Lotka's Lawmentioning
confidence: 99%
“…The constant C corresponds to the number of authors who have contributed to the field only once, as in Serenko and Bontis (2004). The start and end point of the time period of investigation are arbitrary as a matter of principle (Wagner-Döbler and Berg 1995).…”
Section: Lotka's Lawmentioning
confidence: 99%
See 1 more Smart Citation